Wastewater Reuse and Management - Sharma, Sanjay K.; Sanghi, Rashmi; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Over the past 50 years the volume of wastewater has grown exponentially as a result of the increasing world population and the expansion of industrial developments. Researchers all over the world have been trying to address this issue suitably in order to fight water scarcity; yet, it is only recently that wastewater recycling has caught their attention as an effective and responsible solution. Wastewater is a resource that can be adequately treated to successfully satisfy most water demands as well as decreasing wastewater discharges and preventing pollution. This book presents the studies of some of the most prestigious international scientists and gathers them in three different sections: Wastewater Management and Reuse, Wastewater Treatment options and Risk Assessment.  The result is an insightful analysis of waste water management, its treatments, and the processes that have been studied, optimized and developed so far to sustain our environment. Wastewater Reuse and Management represents a valuable resource to academic researchers, students, institutions, environmentalists, and anyone interested in environmental policies aimed at safeguarding both the quality and the quantity of water.
PART I: Wastewater Management and reuse -- Wastewater Management Journey – From Indus Valley Civilisation to the Twenty first Century -- Integration of Membrane Processes for Optimal Wastewater Management -- Recent advances in the reuse of wastewaters for promoting sustainable development -- Reducing the Pollution from Tanneries by Processing Wastewater reuse and membrane technologies -- Wastewater Reuse Focused on Industrial Applications -- PART II: Wastewater Treatment Options -- Hazardous Agents in Wastewater – Public Health Impacts and Treatment Options for Safe Disposal and Reuse -- The small-scale approach in wastewater treatment -- Hospital Wastewaters: Quali-quantitative Characterization and for Treatment and Disposal -- Advances in Mechanical Dewatering of Wastewater Sludge Treatment -- Biosorption of Heavy Metals: Recent trends and Challenges -- Water Desalination by Sola Energy -- AOPs Applications on Dyes Removal -- Constructed wetlands for reducing pesticide inputs into surface water and groundwater -- PART III: Risk Assessment -- Tracing nitrogen sources and cycle in freshwater through Nitrogen and Oxygen isotopic research -- A step-wise approach to assess the fate of nitrogen species in agricultural lowlands -- Environmental risk assessment of WW II shipwreck pollution -- Methods to countermeasure the intrusion of seawater into coastal aquifer systems.
Keywords: Water pollution; Water-supply.; Sustainable development; Waste management; Chemical engineering; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Industry/Water Technologies; Sustainable Development; Waste Management/Waste Technology; Industrial Chemistry/Chemical Engineering